2021
DOI: 10.1111/febs.15789
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the sugar acid‐binding protein CxaP from a TRAP transporter in Advenella mimigardefordensis strain DPN7T

Abstract: Recently, CxaP, a sugar acid substrate binding protein (SBP) from Advenella mimigardefordensis strain DPN7 T was identified as part of a novel sugar uptake strategy. In the current study, the protein was successfully crystallized. Although several SBP structures of TRAP transporters have already been solved, this is the first structure of an SBP accepting multiple sugar acid ligands. Protein crystals were obtained with bound D-xylonic acid, D-fuconic acid Dgalactonic and D-gluconic acid, respectively. The prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…The vast majority of our understanding of TRAP transporter structure and function comes from the characterization of DctP-type TRAP transporters 4,[7][8][9][10][11][12][13][14][15][16][17][18][19][20] , most prominently, a sialic acid-specific member from Haemophilus influenzae, SiaPQM (HiSiaP is the SBP and HiSiaQM is the fused membrane component) 3,[20][21][22][23][24][25][26] . Work from multiple labs on a variety of TRAP SBPs has revealed that, like SBPs from ATP-binding cassette (ABC) transporters, they utilize a venus flytrap type mechanism, in which the binding of ligand to the open apo state triggers closure of the two α/β globular domains around the substrate 27 .…”
Section: Introductionmentioning
confidence: 99%
“…The vast majority of our understanding of TRAP transporter structure and function comes from the characterization of DctP-type TRAP transporters 4,[7][8][9][10][11][12][13][14][15][16][17][18][19][20] , most prominently, a sialic acid-specific member from Haemophilus influenzae, SiaPQM (HiSiaP is the SBP and HiSiaQM is the fused membrane component) 3,[20][21][22][23][24][25][26] . Work from multiple labs on a variety of TRAP SBPs has revealed that, like SBPs from ATP-binding cassette (ABC) transporters, they utilize a venus flytrap type mechanism, in which the binding of ligand to the open apo state triggers closure of the two α/β globular domains around the substrate 27 .…”
Section: Introductionmentioning
confidence: 99%